Molecular identification of all life stages of the predatory mite Iphiseius degenerans (Acari: Phytoseiidae) using 12S rDNA. Issue 7 (2nd October 2016) - Evangelou, Vasiliki I.; Bouga, Maria; Papadoulis, Georgios Th.
ABSTRACT: The use of phytoseiid mites in biological control programmes often requires monitoring at the species level, but typically only adults can be identified using classical taxonomy. In contrast, molecular markers can be applied to identify the species of an arthropod throughout its life history. Individuals of Iphiseius degenerans (Berlese) (Acari: Phytoseiidae) identified according to adult morphological features were reared on almond pollen and kept at 25°C, 65% and HR, 16:8. High quality and quantity of DNA was successfully extracted from all life stages (egg, larva, protonymph, deutonymph, adult male and female) using Phosphate Buffered Saline (PBS) buffer. Sequencing analysis was performed on the 12S rDNA mitochondrial DNA (mtDNA) gene. The authenticity of the new sequences from all life stages was verified as I. degenerans in GenBank (NCBI) confirming that both the DNA extraction method and 12SrDNA gene provide an effective tool for identification of phytoseiid life stages in biological control programmes.